Implementasi Kebijakan Bantuan Sosial untuk Menginvestigasi Ketidaktepatan Sasaran Bantuan Sosial di Desa Rancaekek Kulon Kabupaten Bandung - Nunung, Ai; Latifah, Latifah; Fatmawati, Fatmawati; Sulastri, Lalas (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2025)
This study applies public policy to investigate the inaccuracy of targeting in the distribution of social assistance in Rancaekek Kulon Village, Bandung Regency. The purpose of this study is to find out how the implementation of social assistance policies is carried out in Rancaekek Kulon Village, what are the factors that cause inaccuracy in targeting in the distribution of social assistance and what is the role of village officials, implementing institutions, and the community in the process of data collection and distribution of social assistance. This study is qualitative and uses primary data with three categories, namely structured, semi-structured, and unstructured interviews, the aim is to understand how the implementation of policies and factors that support or hinder inaccuracy of targeting, including deficiencies in the recipient identification process and the role of village officials. The results of the study showed that there was no data update causing inaccuracy in the distribution of social assistance to the poor, this was due to inadequate implementing personnel, weak coordination between organizations and the implementing structure was not optimal, causing inaccurate targeting of social assistance distribution, so this led to a lack of public trust in village implementers. These findings are expected to provide guidance for stakeholders in improving the implementation of public policies in the distribution of social assistance in Rancaekek Kulon Village, Bandung Regency. Keywords: Implementation of public policy, inappropriate targeting, social assistance